Un paysage hydraulique en mutation - Van Hoan Nguyen (Projets de Paysage)
In a context of rapid urban growth, Hanoi, the capital of Vietnam, is an example of urban modernisation. At the heart of this hydraulic city nestled in the meander of the Red River and dotted with a hundred lakes, the urban landscape of Hanoi is changing rapidly under the impact of a major transformation of the lake areas. The lakes are under threat due to the massive presence of landfills. They are polluted and some of them have already disappeared. Based on field research and the study of maps, the article describes the changes in the aquatic surfaces during the transformation of the Hanoi area as well as the strategies adopted by the city to address the problem of their disappearance. Those which remain continue to provide a fundamental contribution to the spatial identity of the city.